Pengaruh Kompetensi SDM terhadap Kualitas Laporan Keuangan SKPD - Muhammad Fakhri; Lili Indrawati; Etti Ernita Sembiring (Indonesian Accounting Research Journal, 2021)
In the Regional Government Financial Report (LKPD) of West Bandung Regency, there are still problems with the accounting and reporting control system. This is due to the fact the local government is still not supported by human resources who have competence in the field of accounting. The purpose of this study was to examine the effect of human resources (SDM) competency on the quality of the financial reports of the Regional Work Units (SKPD) in the Government of West Bandung Regency. This type of study uses a descriptive quantitative survey method. The data used are sourced from primary data obtained directly from respondents. The sample used was 28 SKPD using purposive sampling technique with SKPD criteria located in the West Bandung Regency Government. The data collection method is field research using questionnaires. Data analysis used is simple regression analysis that’s processed using SPSS software program version 24.0. The results of this examine imply that the competence of human resources has a positive and significant effect on the quality of SKPD's financial reports. The importance of the effect of human resource competency on the quality of SKPD's financial reports is 44%, while the remaining 56% is encourage by different variables not tested.